Perancangan Sistem Pemesanan Menu Makanan Dan Minuman Menggunakan QR Code (Studi Kasus: Kedai Lazida Banjarnegara) - Fresi Luviana; Purwanto Purwanto (Journal Of Informatics And Busisnes, 2025)
This research was motivated by the need to improve efficiency and convenience in the food ordering process in the digital era. The manual system currently used at Kedai Lazida is considered ineffective due to long queues, recording errors, and the lack of documentation of customer reviews. Therefore, this study aims to design a web-based food and beverage ordering system with QR Code integration to make the service process faster, more modern, and interactive. The method used in this research is prototyping, which consists of the stages of needs identification, system design, prototype development, user evaluation, and system refinement. The designed system includes various features such as customer login via QR Code, menu selection, order basket, cash and digital payment methods, and a review feature with ratings. Data was collected through direct observation, interviews with the shop staff, and literature review of relevant previous research. The results show that the designed system is able to address the primary needs of customers and shop managers by speeding up the ordering process, improving the user experience, and providing a platform for service evaluation through customer reviews. This system also provides an innovative solution for culinary MSMEs in adopting digital services in a practical and affordable way. With further implementation, this system is expected to improve operational efficiency and the overall service quality of Kedai Lazida.